(untitled) (IITM Journal of Business Studies, 2024)
Through the book "Building the Internet of Things", Author Maciej Kranz, Vice President of the Strategic Innovations Group at Cisco aims to bring the knowledge of rhe "Intcrner ofThings" (loT) in rhe minds of the Present Business Managers and the potential Managers of the Fumre. Right from the first Chapter of the Book, Kranz tells us why IoT is essemial in roday’s world, and how it is capable of shaping the future of Business Organizations.